Total phenolic content, flavonoid content, and antioxidant capacity of Syzygium. cumini (L.) Skeels leaves grown in Wonosobo, Java, Indonesia and comparison against current findings of Syzygium cumini leaves and Syzygium polyanthum (Wight) Walp leaves - Sukmasari, Susi; Mohd, Farah Natashah; Doolaanea, Abd Almonem; Abdul Qader, Omar Abdul Jabbar; Abdul Rahman, Mohammad Nasrin (PharmaInfo Publications, 2018)
Objective: To investigate the total phenolic and flavonoid content and antioxidant capacity of Syzygium cumini grown in Wonosobo, Central Java, Indonesia. The findings will be used to compare similarities and differences with other current findings for Syzygium cumini leaves and Syzygium polyanthum leaves. Methods: Syzygium cumini was extracted using sequential cold percolation method. Total phenolic and flavonoid content were quantified using Folin-Ciocalteu and down colorimetric method, respectively. Antioxidant capacity was quantified by measuring scavenging activity of extracts towards DPPH radicals (DPPH assay), as well as FRAP assay to measure the extract’s reducing power. Results: In the present study, Syzygium cumini water extract had the best percentage yield (4.83 ± 0.32 %), total phenolic content (40.94 ± 9.79 mg GAE/g DW), and antioxidant capacity (both DPPH and FRAP test) compared to other extracts (petroleum ether, toluene, ethyl acetate, and acetone). Toluene extract was found to contain the highest total flavonoid content with value of 42.90 ± 8.64 mg QE/g DW. Comparing with other current findings, various similarities and differences were found between intra species (Syzygium cumini from different locations) and interspecies (Syzygium cumini and Syzygium polyanthum). Conclusion: Total phenolic, flavonoid contents and antioxidant capacity of Syzygium cumini collected in Indonesia were successfully investigated. There are also a lot of similarities and differences between species of Syzygium cumini and Syzygium polyanthum.